Proceedings of the IFPRI-AERA policy dialogue on “Transforming Agri-Value Chains: Emerging Frontiers for Agribusiness” - Mohan, Anisha; Alagh, Munish; Sirsikar, Ishita (International Food Policy Research Institute, 2026)
Transforming agri-value chains has emerged as a central policy challenge for India as agriculture shifts from a primary production-oriented sector to one that is increasingly shaped by markets, value additions and consumer demand. Moreover, as agriculture becomes increasingly integrated with markets, technology, finance and services, the role of agribusiness and value-chain institutions in shaping development outcomes has grown both in scale and complexity.